Analisis Green Repurchase Intention Gen-Z Dalam Perspektif Gender - Pranatasari, Fransisca Desiana; Wadyatenti, Maria Angela Diva Vilaningrum; Ismawati, Anastasia Filiana (Business Management Journal, 2025)
Eco-friendly products are a sustainable future solution. With the concept of green repurchase intention, consumers are involved in efforts to achieve SDG's. Green repurchase intention is part of the concept of sustainable consumption that is in line with the pillars of the Universal Apostolic Preferences (UAP). The big challenge is the awareness of environmentally friendly products which is minimal in number. Generation Z is believed to have the ability to support sustainable social movements because they tend to care more about sustainability and environmental issues. Generation Z is the right object because it has great potential to become agents of change individually and collectively in creating a better world. The purpose of the study was to analyze the influence of green perceived value and green WOM on green repurchase intention with green trust as a mediator. Furthermore, researchers also looked at differences in gender perspectives. The research method used instrument testing through validity and reliability tests, Measurement Models (Outer Models), Structural Models (Inner Models), and hypothesis testing. In the second stage, a difference test was carried out for gender perspectives using the independent t-test analysis technique. The results are expected to contribute to science related to the triggers of the process that lead to the intention to repurchase environmentally friendly products so that the future of the earth and its environment can be well maintained. The study obtained results on factors that influence green repurchase intention among Generation Z. Through a gender perspective difference test, the study also provides a contribution to the marketing field on green repurchase intention, especially related to consumption patterns and prioritized values.